A rare case of acquired lymphangioma circumscriptum of the penis. (February 2017) - Adikari, S; Philippidou, M; Samuel, M
Acquired lymphangioma circumscriptum is a rare occurrence on the penis. We report a case of a 47-year-old man who presented with a single lesion of acquired lymphangioma circumscriptum on the penis resembling genital warts. We report the case to increase awareness of this rare condition which may mimic sexually transmitted infections such as genital warts.